Colombia: aumento de las exportaciones y sus efectos sobre el crecimiento, empleo y pobreza - Fabio José, Sánchez; Gustavo Adolfo, Hernández (Desarrollo y Sociedad, 2004)
Colombia reduced import protection along with explicit export promotion schemes in the early 1990s. Capital flows were liberalized although some restrictions on short-term inflows were retained to reduce volatility. Output growth was led by exports in the second half of the 1980s, but the rise in capital inflows and the related real exchange rate appreciation, triggered a domestic demand boom for nontraded goods in the early 1990s. Public spending in particular was up in this period and jumped from 20% to 36% of GDP between 1990 and 1999. In the first half of the decade, economic growth accelerated to 4.6% per annum. This ‘go’ phase of the economy was followed by a prolonged ‘stop’ after 1997. The economy shrank between 1997 and 2000 mainly due to a collapse of private investment. Non-traditional export growth had been the engine of the economy in the late 1980s, but manufacturing exports actually declined during 1997-2000. Nonetheless, manufactured exports now constitute more than 50% of total exports (up from 27% around 1980), as the decline in traditional exports (most notably, coffee) was even more severe. The share of coffee in total exports dropped from 60% to barely 10% between 1977-2000 and coffee exports suffered a major crisis after 1997. The capacity of the economy to generate jobs deteriorated notably. Productivity growth during the first years of the opening process implied virtually no employment growth in the first half of the 1990s, but average real wages could increase. The decline of the economy in the second half affected workers severely and by 2000 the open unemployment rate was up at an unprecedented 20%. The poor employment performance hit unskilled workers hardest. As a result income inequality has increased steeply and the Gini coefficient moved up from 0,467 to 0,544 between 1990 and 2000, mainly as the result of a widening earnings gap between skilled and unskilled workers. In consequence, economic growth did virtually nothing to reduce poverty. Simulations with a CGE for Colombia suggest that these trends are not due to static gains (or losses) from trade liberalization. Further trade liberalization (unilateral or negotiated in the context of FTAA or WTO) appears mildly positive for economic growth and labour incomes. Labour income gains seem mainly concentrated among unskilled workers. Hence, it wasn’t trade reform, but macroeconomic policies and external shocks which pushed the economy and poverty down and inequality up.